Stability Analysis of a Hybrid Multi-Infeed HVdc System Connected Between Two Offshore Wind Farms and Two Power Grids - Li Wang; Zhi-Hao Yang; Xiu-Yu Lu; Prokhorov A. V. Anton Viktorovich (2017, 2017)
Title screen